One optometrist’s personal experience with age-related macular degeneration (AMD) and nutritional supplementation - Richer, Stuart; Licup, Albert; Porter, Tere; Collison, Frederick (Canadian Journal of Optometry, 2012)
Background: Age-related macular degeneration (AMD) is the leading cause of blindness in ageing western societies and accounts for greater than 50% of all US visual disability. This report describes the 25-year history of a 66-year-old optometrist who has successfully endured AMD. Case Report: Visual acuity and serial retinal photographs from 1983 to 2009 as various nutritional modalities and non-dietary lifestyle changes were introduced. After starting lutein-based nutritional supplements beginning at approximately 15 years from diagnosis, the optometrist’s Snellen visual acuity improved in his right eye from 20/40 to 20/25 with a subjective improvement in distortion, but eventually regressed to 20/70-20/80 with some increase in metamorphopsia. The left eye, initially 20/30, improved to 20/15 and has remained stable at 20/20 with complete resolution of metamorphopsia and near complete resolution of a parafoveal scotoma. Fundus photographs demonstrate a reduction in soft and hard drusen count over time in each retina and possible parafoveal repigmentation of atrophic areas with later addition of higher dose zeaxanthin. Conclusions: AMD is a nutritionresponsive disease. The carotenoids, lutein and zeaxanthin appear to be particularly robust therapeutic components of nutritional supplement formulations.